Praktek Pemilahan Sampah untuk Meningkatkan Kepedulian Lingkungan Bagi Siswa Sekolah Dasar di Desa Molotabu, Kabupaten Bone Bolango - Maryati, Sri; Batjoli, Muh Fajri; Tahir, Ronal; Limonu, Rusli (Universitas Negeri Gorontalo, 2024)
WASTE SORTING PRACTICES TO ENHANCE ENVIRONMENTAL AWARENESS FOR ELEMENTARY SCHOOL STUDENTS IN MOLOTABU VILLAGE, BONE BOLANGO REGENCY. Waste management issues in coastal areas have become an urgent environmental concern that requires immediate attention. In coastal areas that serve as tourist destinations, waste can pollute the environment, damage marine ecosystems, and reduce the attractiveness of tourism. The waste sorting practice activity for elementary school students aims to increase their environmental awareness. This activity includes pre-test stages, material delivery, waste sorting practice, and post-test evaluation. The results show a significant improvement in students' understanding, especially in distinguishing organic and inorganic waste, with a 77% increase. Students demonstrated a positive attitude toward waste sorting and involved their families. Practice-based environmental education has proven effective in forming positive habits from an early stage, which is expected to contribute to sustainable waste management in coastal areas.